2024
DOI: 10.1111/nin.12622
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing spiritual care: Discursive underpinnings within palliative care research

Emma Lundberg,
Joakim Öhlén,
Lisen Dellenborg
et al.

Abstract: Religion and spirituality are integral to the philosophy of palliative care, shaping its approach to spiritual care. This article aims to examine the discourses within palliative care research to illuminate prevailing assumptions regarding spiritual care. Eighteen original articles were analyzed to examine how spiritual care is understood within palliative care. The analysis, informed by Foucault, aimed to identify recurring discourses. The finding reveals that, in palliative care research, spirituality is vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…In palliative care, respecting patients’ religious beliefs and providing spiritual care has become the norm in the bio-psycho-social-spiritual model of medical care. 38 , 39 Although the medical model for patients also uses the bio-psycho-social-spiritual model to provide medical treatment, it pays less attention to spiritual care, and there is not enough research on the relationship between religion and spiritual care. This study found that there are statistical differences in the lower spiritual well-being of patients with different religious beliefs, especially among the large number of patients with Taoist and folk beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…In palliative care, respecting patients’ religious beliefs and providing spiritual care has become the norm in the bio-psycho-social-spiritual model of medical care. 38 , 39 Although the medical model for patients also uses the bio-psycho-social-spiritual model to provide medical treatment, it pays less attention to spiritual care, and there is not enough research on the relationship between religion and spiritual care. This study found that there are statistical differences in the lower spiritual well-being of patients with different religious beliefs, especially among the large number of patients with Taoist and folk beliefs.…”
Section: Discussionmentioning
confidence: 99%